Faktor Determinan Upaya Promosi Kesehatan Berbasis Choaching untuk Upaya Pencegahan Diabetes Melitus Tipe 2 - Sunarto Sunarto; Sudiro Sudiro; Addi Mardi Harnanto (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a growing public health problem, largely driven by modifiable risk factors. Health coaching has emerged as a promising health promotion approach to facilitate healthy behavior change; however, evidence regarding determinants of its success in community-based T2DM prevention remains limited. Objectives: To identify the determinants of health coaching-based health promotion in preventing T2DM among at-risk community members. Methods: A quasi-experimental pretest-posttest control group study was conducted among 52 individuals at risk of T2DM participating in community-based non-communicable disease screening programs in Surakarta, Indonesia. Participants were allocated into an intervention group (n=26) receiving a six-month community-based health coaching program and a control group (n=26) receiving standard health education. T2DM risk was assessed using the Finnish Diabetes Risk Score (FINDRISC). Data were analyzed using Chi-square/Fisher’s Exact Test and multiple logistic regression. Results: Baseline characteristics were comparable between groups. Bivariate analysis showed significantly greater improvements in physical activity (53.8% vs 19.2%; p=0.011) and fruit and vegetable consumption (57.7% vs 23.1%; p=0.012) in the health coaching group compared with the control group. Multivariate analysis identified health coaching as the strongest determinant of successful T2DM risk reduction (OR=6.65; 95%CI=2.12–20.78; p=0.001). Increased physical activity (OR=3.37; p=0.018) and improved fruit and vegetable consumption (OR=2.60; p=0.043) were also significant predictors of risk reduction. Conclusion: Health coaching-based health promotion is an effective strategy for T2DM prevention and represents the strongest determinant of diabetes risk reduction through improvements in physical activity and fruit and vegetable consumption among at-risk populations. Keywords: Type 2 Diabetes Mellitus, Health Coaching, Health Promotion, Determinants, FINDRISC.